2021
DOI: 10.15184/aqy.2021.153
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Karakorum, the capital of the Mongol Empire

Abstract: In the thirteenth century AD, the city of Karakorum was founded as the capital of the Mongol Empire. Relatively little archaeological attention, however, has been directed at the site and the phenomenon of steppe urbanism. The authors report new magnetic and topographic surveys of the walled city and the surrounding landscape. The resulting maps reveal the city in unprecedented detail. Combining the magnetic and topographical data with aerial photographs, pedestrian surveys and documentary sources reveals the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…According to the written sources, the urban space of Karakorum was dominated by palaces along with religious buildings, gardens, streets, squares, the quarters of traders and craftsmen, and the quarters of Saracens and Nestorians, and those of Mongols. 23,24 The city map (Figure 4) shows that the city was surrounded by mud walls and divided by two main streets running N-S and E-W and leading towards the four main gates. These large main roads divided the city into four quarters, and they lead beyond city limits.…”
Section: City Layoutmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the written sources, the urban space of Karakorum was dominated by palaces along with religious buildings, gardens, streets, squares, the quarters of traders and craftsmen, and the quarters of Saracens and Nestorians, and those of Mongols. 23,24 The city map (Figure 4) shows that the city was surrounded by mud walls and divided by two main streets running N-S and E-W and leading towards the four main gates. These large main roads divided the city into four quarters, and they lead beyond city limits.…”
Section: City Layoutmentioning
confidence: 99%
“…The general layout of the city is as shown in Figure 13; the locations of the streets and roads are decided based on the studies reported in References 22,23. Some structures or monuments such as the Great Buddhist Temple and the Stone turtle statue were established on the site based on archeological excavations.…”
Section: City Layoutmentioning
confidence: 99%
“…История показывает, что на территории азиатских государств Центральной Азии сложились поликультурные типы жилых сред и жилых комплексов: греко-бактрийский, тюрко-согдийский, мусульманский, буддийский, ки-вья -Сокулукского, Сретенского, Телека, Кен-Булуна [2]. Наиболее интересным стало исследование монгольского города Каракорум Кембриджским университетом с использованием цифровых инструментов, которое «концептуализируется как форма "имплантированного" урбанизма» [3]. Сочетание магнитных и топографических съемок позволило повысить детализацию генерального плана города Каракорума, что открывает новые возможности для изучения местности.…”
unclassified